Dismantling the Master’s House: Toward Epistemologies of Resistance and Freedom Dreaming - Dutta, Urmitapa (PINS-Psychology in Society, 2024)
What does it mean to reimagine inquiry in psychology as the academy, nation state regimes, and markets discipline the terms of what it means to be human? Drawing upon the wisdom of Black, Indigenous, Palestinian, and other feminists of color, I explore what it means to bear faithful witness to (settler) colonial violence and genocide. Situated in the context of Israeli settler colonial occupation and the persecution of Palestinian knowledge traditions and knowledge keepers, this article strives to chart a defiant methodology that resists analytic closure. Reflecting on scenes from occupied Palestine and weaving together insights from decolonial scholar-activists, I center the body as insurgent knowledge and method to counter settler colonial logics of elimination and erasure. Simultaneously, I explore freedom dreams as embodied, emancipatory wisdom and abolitionist inquiry. Across these critical engagements, I contend with the kinds of radical re-imaginings and paradigmatic shifts that freedom dreams call for. Do we dare to rethink social inquiry as radical imaginary praxis – an antidote to indifference and atrophying revolutionary sensibilities? Grappling with these issues, I advocate for inquiry as a combative praxis aligned with the material demands of decolonization, striving to unleash our radical imaginaries toward building pluriversal, liberated futures.